Logic, thought, and language - O'Hear, Anthony (Cambridge University Press, 2002)
Much contemporary philosophical debate centres on the topics of logic, thought and language, and on the connections between these topics. This collection of articles is based on the Royal Institute of Philosophy's annual lecture series for 2000-2001. Its contributors include a number of those working at the forefront of the field, and in their papers they reflect their own current pre-occupations. As such, the volume will be of interest to all philosophers, whether their own work is within the areas of language and thought or not